Effects of Valence and Origin of Emotions in Word Processing Evidenced by Event Related Potential Correlates in a Lexical Decision Task - Imbir, Kamil K.; Spustek, Tomasz; Żygierewicz, Jarosław (Frontiers in Psychology, 2016)
This paper presents behavioral and event-related potential (ERP) correlates of emotional word processing during a lexical decision task (LDT). We showed that valence and origin (two distinct affective properties of stimuli) help to account for the ERP correlates of LDT. The origin of emotion is a factor derived from the emotion duality model. This model distinguishes between the automatic and controlled elicitation of emotional states. The subjects’ task was to discriminate words from pseudo-words. The stimulus words were carefully selected to differ with respect to valence and origin whilst being matched with respect to arousal, concreteness, length and frequency in natural language. Pseudo-words were matched to words with respect to length. The subjects were 32 individuals aged from 19 to 26 years who were invited to participate in an EEG study of lexical decision making. They evaluated a list of words and pseudo-words. We found that valence modulated the amplitude of the FN400 component (290-375ms) at centro-frontal (Fz, Cz) region, whereas origin modulated the amplitude of the component in the LPC latency range (375-670ms). The results indicate that the origin of stimuli should be taken into consideration while deliberating on the processing of emotional words.